The degree of application of government secondary school principals in Deir Alla district in Jordan to the strategy of self-management and its relationship to administrative creativity from the point of view of teachers - Rashid, Badeah Ali (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the degree of application of government secondary school principals in Deir Alla district in Jordan to the self-management strategy and its relationship to administrative creativity from the teachers’ point of view. This study used the descriptive associative method. Where a questionnaire was prepared in order to measure the degree of application of the self-management strategy. The study population consisted of all secondary school teachers in the Directorate of Education in Deir Allah (2019/2020). The study sample was chosen by stratified random method, and the results of the study showed that the arithmetic averages of the study sample’s estimates for each dimension of the field of self-management ranged between (3.87-3.96) with a high evaluation degree for all dimensions, where the “follow-up and evaluation” dimension came in first place. With an arithmetic average (3.96), it came in second place after "delegating authority" with a arithmetic mean (3.89), and ranked third and last after "professional growth" with an arithmetic mean (3.87), and the arithmetic average for the field as a whole was (3.90) with a high evaluation score as well, and there is a relationship Positive correlation between strategy. Self-management and application of administrative creativity skills for secondary school principals in Deir Alla Education Directorate. In light of these results, the study recommends spreading the organizational culture to implement the self-management strategy. The directorates of education must provide the requirements for implementing the self-management strategy and pay attention to the school’s infrastructure and technology to improve administrative, technical and social communication so that it can practice self-management for this and the skills of administrative creativity.